ANALISIS PENGARUH ARUS KAS, PERPUTARAN PIUTANG DAN PERPUTARAN MODAL KERJA TERHADAP LIKUIDITAS PT. VALMATIC INDONESIA PERIODE 2015-2019 - jessy; Sutanto, Hermawan (Jurnal Manajemen Akuntansi Dan Administrasi Bisnis, 2021)
This study aims to examine and analyze the effect of cash flow, accounts receivable turnover and working capital turnover partially and simultaneously on liquidity at PT. Valmatic Indonesia for the 2015-2019 period. This research was conducted at PT. Valmatic Indonesia by taking the 2015-2019 financial statements as the object of research. The population and samples used are 60 data. The data analysis technique used descriptive statistics, classical assumption test and multiple linear regression analysis. The results of the study partially show that cash flow has a positive and significant effect on liquidity, accounts receivable turnover has no effect on liquidity and working capital turnover has a positive effect on liquidity. Simultaneously the three variables, namely cash flow, accounts receivable turnover and working capital turnover have a significant effect on the liquidity of PT. Valmatic Indonesia, as for the magnitude of the influence of the three variables seen from the value of the Adjusted R Square, which is 38.8%.